The Role of Partial Breast Radiation in the Previously Radiated Breast. (December 2019) - Korzets, Yasmin; Lee, Grace; Espin-Garcia, Osvaldo; Purdie, Thomas; Koch, Anne C.; Hodgson, David; Barry, Aisling; Fyles, Anthony
Abstract : Objectives: The aim of this study was to analyze breast cancer patients who previously had mantle-field or breast radiation (RT) followed by retreatment with external beam partial breast irradiation (EB PBI). Materials and Methods: We retrospectively reviewed all women with newly diagnosed early-stage breast cancer treated with lumpectomy and partial breast irradiation between 2007 and 2017 who had undergone prior chest or breast RT. Results: Of 11 patients recorded, 8 (73%) had Hodgkin lymphoma, and 3 (27%) had ipsilateral breast cancer diagnosis. Median age at initial and second diagnosis was 28 and 48 years, respectively. The lymphoma patients received a dose of 35 Gy in 16 to 20 fractions to a classic mantle-upper abdomen field. Patients with an initial diagnosis of breast cancer received whole-breast RT (2 with 50 Gy/25 fractions, 1 with 40 Gy in 16 fractions). Median time from initial to second diagnosis was 22.6 years (range, 13.5 to 32.6 y). All had early-stage (I to II) invasive ductal carcinoma and were treated with lumpectomy or repeat lumpectomy and EB PBI. Four received a dose of 45 Gy/25 fractions, 4 to 50 Gy/25 fractions, and 3 to 42.4 Gy/16 fractions. All patients received adjuvant systemic treatment. Two patients had toxicity, 1 had grade 1 induration, and the other had grade 2 fat atrophy and grade 1 fibrosis. One patient developed a contralateral breast cancer. No locoregional recurrences were reported at the median follow-up of 4.6 years (range, 0.6 to 10.5 y). Conclusion: EB PBI after lumpectomy seems to be a safe and effective RT treatment option for selected patients with prior RT and localized early-stage breast cancer.